The Influence of Workload, Work Stress and Motivation on Turnover Intention: (Study of PT. "X" Employees) - Junaedi Junaedi; Ozzamma Syahputra (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This research was conducted with the aim of analyzing the influence of workload, work stress, and motivation on turnover intention among PT employees. "X". A total of 78 employees of PT. “X” were the respondents in this research using the saturated sample method. This research uses Structural Equation Model (SEM) data analysis techniques and data processing using Partial Least Square (PLS). The results of this research show that workload and work stress have a positive and significant effect on turnover intention and motivation has a positive and significant effect on turnover intention. The managerial implications of the findings in this research recommend that leaders reduce employee overtime, apart from that PT. “X” is also recommended to reduce too many task demands, and finally PT. “X” is also recommended to increase motivation to work even more enthusiastically.